Research on optimal allocation of surface ship formation based on index method and multi-objective programming - Guo, Zilong; Hong, Mei; Shi, Jian; Zhang, Yongchui; Qian, Longxia; Li, Hanlin (Ocean engineering, 2024)
In recent times, marine engineers have progressively turned to collaborative efforts involving multiple ships to accomplish intricate tasks at sea and enhance the efficacy of maritime transportation. This trend is also observed in the context of surface ships, where coordinated actions among multiple vessels can enhance combat capabilities. Nevertheless, the assessment of ship formation coordination’s effectiveness has emerged as a significant challenge. Consequently, this research paper presents a quantitative evaluation framework for ship performance indicators and develops a ship formation model grounded in multi-objective constraints that account for the complexities of the marine environment. This paper presents the establishment of a ship evaluation system that encompasses the impact of auxiliary equipment, the ship’s platform, and trained personnel. The study utilizes aircraft carrier battle groups from four distinct countries as case examples to obtain quantitative evaluation results regarding combat performance. Furthermore, the analysis examines the effects of two extreme marine environments on surface ships. The organization of new surface ship formations is conducted based on a multi-objective planning model that is tailored to specific surface ship formations. All kinds of combat performance indexes are better than the formation of this particular surface ship. The experimental results show that the model can integrate different kinds of equipment performance parameters into a unified system and consider the comprehensive factors of equipment, platform and people. According to the requirements of task formation and the limitations of the actual Marine environment, a stable formation can be formed quickly, which can be superior to a specific formation in all aspects. Good results are obtained and the effectiveness of the model is verified. •We quantitatively assessed the operational effectiveness of the ship formation.•Different kinds of parameters are incorporated into a unified system.•The final result accords with the actual formation efficiency through comparative analysis.•Multi-objective programming model is used for autonomous formation research.